COMPARATIVE STUDY OF TEACHING APPROACHES (SCIENCE TIME JOURNAL, 2026)
The debate between teacher-centered and student-centered approaches has become one of the most significant issues in modern education. Traditional teacher-centered instruction emphasizes the authority of the teacher, structured lessons, and knowledge transmission, whereas student-centered learning focuses on learners’ autonomy, active participation, and critical thinking. This article compares these two educational approaches by examining their characteristics, advantages, disadvantages, and influence on students’ academic performance and motivation. Using qualitative analysis of educational literature and classroom practices, the study highlights the strengths and limitations of both methods.